Analog-digital wide-range measurement systems with adaptively adjusted quartz glass sensors - Szabatin, J.; Melnikov, V.E.; Platonov, A.A. (1996 IEEE Instrumentation and Measurement Technology Conference Proceedings, 1996)
In this paper, a new class of smart analog-digital systems for measurement of acceleration, displacement, size, weight, pressure, and other quantities, is considered. Theoretical basics and practical ways of realizing such systems are presented. Techno-economic and technological characteristics as well as possibilities of production of these systems are also discussed. Their principal feature is that they employ sensors whose parameters can be adjusted adaptively to the statistics of a measured process. Introducing appropriate modifications into conventional sensors, this enables us at no great expense to considerably extend the dynamic range of measurements as well as to increase their accuracy. With a view to superior quality characteristics and low cost, as a reference point for designing this class of measurement systems, electromechanical sensors based on quartz glass technology are chosen.